A Daylength Recognition Model of Photoperiodic Flowering - Wang, Xiaoying; Zhou, Peng; Huang, Rongyu; Zhang, Jianfu; Ouyang, Xinhao (Frontiers in Plant Science, 2021)
The photoperiodic flowering pathway is crucial for plant development to synchronize internal signaling events and external seasons. One hundred years after photoperiodic flowering was discovered, the underlying core signaling network has been elucidated in model plants such as Arabidopsis (Arabidopsis thaliana), rice (Oryza sativa), and soybean (Glycine max). Here, we review the progress made in the photoperiodic flowering area and summarize previously accepted photoperiodic flowering models. We then introduce a new model based on daylength recognition by florigen. By determining the expression levels of the florigen gene, this model can assess the mechanism of daylength sensing and crop latitude adaptation. Future applications of this model under the constraints of global climate change are discussed.